2015
DOI: 10.1109/tcsvt.2014.2367354
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Rate Control Framework for SIFT/SURF Feature Preservation in H.264/AVC Video Compression

Abstract: This paper presents a novel rate control framework for H.264/Advanced Video Coding-based video coding that improves the preservation of gradient-based features like scale-invariant feature transform or speeded up robust feature compared with the default rate control algorithm in the JM reference software. First, a criterion (matching score) for feature preservation on the basis of the bag-of-features concept is proposed. Then, the matching scores are collected as a function of the quantization parameters and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 43 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…The compressed images are transmitted via a wireless network to a server where features are extracted. In our previous work [14], we have observed that for feature-preserving image/video compression, the keypoint detection is easily affected by compression artifacts, while the descriptor calculation is more robust. To address this issue, we investigate in this paper whether explicit signaling of keypoint information (location, scale, and orientation) improves the quality of features which are extracted from the compressed images.…”
Section: Introductionmentioning
confidence: 99%
“…The compressed images are transmitted via a wireless network to a server where features are extracted. In our previous work [14], we have observed that for feature-preserving image/video compression, the keypoint detection is easily affected by compression artifacts, while the descriptor calculation is more robust. To address this issue, we investigate in this paper whether explicit signaling of keypoint information (location, scale, and orientation) improves the quality of features which are extracted from the compressed images.…”
Section: Introductionmentioning
confidence: 99%
“…SURF approximates or even outperforms a previously proposed SIFT algorithm [28,29], which is patented, with respect to repeatability, distinctiveness, and robustness, yet can be computed and compared much faster. Thus, the method posited here improves feature extraction speed.…”
Section: Feature Extractionmentioning
confidence: 99%
“…Most feature vectors are either global vectors, such as a global color histogram, or local vectors such as SIFT descriptors [28,29] and SURF descriptors [6,7]. The first model generates an extreme compressed feature vector for each image.…”
Section: Feature Extractionmentioning
confidence: 99%
“…The motivation is that gradients are useful features in a number of computer vision problems, so well-preserved gradients will likely improve the accuracy of the vision pipeline. Another recent work [6] develops a rate control scheme for H.264/AVC video coding that preserves SIFT [7] and SURF [8] features, which have also been found useful in many computer vision problems. These studies ( [5,6]) have proposed ways to preserve well-known handcrafted features through the compression process, without focusing on any particular problem.…”
Section: Introductionmentioning
confidence: 99%
“…Another recent work [6] develops a rate control scheme for H.264/AVC video coding that preserves SIFT [7] and SURF [8] features, which have also been found useful in many computer vision problems. These studies ( [5,6]) have proposed ways to preserve well-known handcrafted features through the compression process, without focusing on any particular problem. However, the recent trend in computer vision has been away from handcrafted features and towards learnt features, especially the features learnt by deep neural networks (DNNs) [9] for specific problems.…”
Section: Introductionmentioning
confidence: 99%